Indian Socialist Ideology in Indian Constitution: The Role of Socialism in the Indian Constitution (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The socialism is recognized as Indian political system's cherished goal. Socialism emphasizes people's welfare, seeks to give people equality, and seeks to eliminate the exploitation of one class by the other, and ensures economic and political equality for everyone. This fundamental constitutional concept has been added to give equality and fraternity to the economic content of justice and to affirm the resolve of non-discrimination on the grounds of religion. Socio-economic justice is the pillar of socialism. For this reason, in Part 4 of our Constitution, the framers of our Constitution have prescribed these fundamental principles in the form of the directive principle of state policy to establish a welfare state based on the principles of socialism. All of us need to safeguard the holy spirit of socialism enshrined in our constitution, so that we can achieve all round progress with peace and harmony.